Consumers’ Knowledge, Attitudes and Willingness to Pay for Bio–Plastic Packaging - Davivongs, Kuntonrat; Potchanasin, Chakrit; Athipanyakul, Thanaporn; Nantajit, Chompunuch (Journal of Applied Economics and Management Strategy, 2023)
Bio-plastic packaging is a co-product from cane and sugar industry which is consistent with the 20 years National Strategy and the Cane and Sugar Industry Strategy plan as a new S-Curve industry to enhance agricultural product value. However, commercial development of the industry needs more information from the consumers’ side to support development decision and direction. Therefore, this paper aims to investigate behavior, knowledge, and attitudes of the customers towards bio-plastic packaging including analysis of their willingness to pay (WTP). The study used the data collected by interviewing 458 consumer samples in Bangkok, Chiangmai, Khonkaen and Songkhla provinces. Investigation had applied descriptive analysis and double bounded method to evaluate WTP. The study results revealed that the consumers had positive attitude towards bioplastics and had awareness regarding problems from chemical plastic uses. However, the consumers had limited knowledge about bioplastics knowledge. In addition, the consumer WTP was 6.697 Baht per box. Also, the WTP had significantly affected by the factors of consumers’ behavior and awareness regarding to environmental problems. The factors included e.g., waste separation behavior, littering method and general awareness of environment. Hence, policy makers should promote more bioplastic information to the customers and bioplastic entrepreneurs could use WTP result as proxy for cost management and pricing their bio-plastic products accordingly.